Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 2 - Section 2.4 - Signed Fractions - Exercises - Page 118: 14



Work Step by Step

Use the rule $a-(-b) = a+b$ to obtain: $=\left(+2\dfrac{3}{4}\right)+\left(3\dfrac{1}{4}\right) \\=(2+3)+\left(\frac{3}{4}+\frac{1}{4}\right) \\=5+\frac{4}{4} \\=5+1 \\=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.